Effect of sleep deprivation on fractal and oscillatory spectral measures of the sleep EEG: A window on basic regulatory processes - G․ Horváth, Csenge; Bódizs, Róbert (NeuroImage (Orlando, Fla.), 2025)
•The reliable measurement of sleep regulatory processes is indisputable.•Sleep deprivation is an important method challenging the homeostatic process.•NREM sleep EEG spectral slope is a new, standardisable measure of sleep homeostasis.•Spindle frequency reflects putative circadian modulation under baseline conditions.•Sleep homeostasis can be reliably measured in home settings, outside the laboratory. Sleep is vital for sustaining life; therefore, reliable measurement of its regulatory processes is of significant importance in research and medicine. Here we examine the effect of extended wakefulness on the putative indicators of fundamental sleep regulatory processes (spectral slope and spindle frequency) proposed by the Fractal and Oscillatory Adjustment model of sleep regulation by involving a healthy young adult sample in a 35-hour long sleep deprivation protocol. Wearable headband EEG-derived results revealed that NREM sleep electroencephalogram (EEG) spectral slope estimated in the 2–48 Hz range is an accurate indicator of the predicted changes in sleep depth induced by sleep deprivation (steepened slopes in recovery sleep) or by the overnight dissipation of sleep pressure (flattening slopes during successive sleep cycles). While the baseline overnight dynamics of the center frequency of the sleep spindle oscillations followed a U-shaped curve, and the timing of its minimum (the presumed phase indicator) correlated with questionnaire-based chronotype metrics as predicted, a different picture emerged during recovery sleep. Advanced recovery sleep advanced the timing of the minima of the oscillatory spindle frequency, reduced considerably its relationship with chronotype, but retained partially its U-shaped overnight evolution. Overall, our study supports the use of the spectral slope of the sleep EEG as a homeostatic marker of wake-sleep regulation, in addition, encourages further research on the EEG-derived measure of the circadian rhythm, primarily focusing on its interaction with the homeostatic process.